SIFAT FISIK KAYU MANGLID (Manglieta glauca Bl.) PADA ARAH AKSIAL DAN RADIAL - M. Siarudin; Ary Widiyanto (Jurnal Penelitian Hasil Hutan, 2012)
Study on physical properties of manglid (Manglieta glauca Bl) wood on axial and radial orientation has been conducted. Three manglid trees were taken as samples from community forest in Sodongbilir Village, Sodongbilir Sub-district, Tasikmalaya Regency, West Java. The observation focused on physical properties on three positions of both accial orientation (bottom, midle and top of trunk) and radial orientation (near pith, middle and near bark). The parameters observed were fresh moisture content, air dry moisture content, and wood dimensional changes. Result shows that the average of fresh moisture content of manglid wood is 168.77%, air dry moisture content is 14.63%, specific gravity on fresh volume is 0.35, specific gravity on air dry volume is 0.36 and specific gravity kiln dry volume is 0.38. Based on its dimensional changes, manglid wood bas longitudinal shrinkage value of 1.51%, radial shrinkage value of 4.08%, tangential shrinkage value of 5.84%, and ratio of tangential and rudial shrinkage of 1.54. Physical properties of manglid wood on axial and radial orientation are varied for fresh miosture content and specific gravity, while the air dry moisture content and the dimensional changes are not significantly different. The trend of fresh moisture content value on axial orientation is increased from the bottom to the middle of the trunk, and then decreased ot the top of the trunk. On radial orientation, the fresh moisture content value consistently decreases from the pith to towards the bark. Specific grafity value on the axial orientation decreases from the bottom of the trunk to the midle, then increases on the top. In radial orientation, the specific gravity gravity ralue consistently increases from the pith towards the bark.